2019
DOI: 10.1115/1.4043711
|View full text |Cite
|
Sign up to set email alerts
|

Hydrous Ethanol Steam Reforming and Thermochemical Recuperation to Improve Dual-Fuel Diesel Engine Emissions and Efficiency

Abstract: Dual-fuel strategies can enable replacement of diesel fuel with low reactivity biofuels like hydrous ethanol. Previous work has shown that dual-fuel strategies using port injection of hydrous ethanol can replace up to 60% of diesel fuel on an energy basis. However, they yield negligible benefits in NOX emissions, soot emissions, and brake thermal efficiency (BTE) over conventional single fuel diesel operation. Pretreatment of hydrous ethanol through steam reforming before mixing with intake air offers the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Ammonia dual-fuel operation resulted in a sharp decrease in combustion efficiency for all modes, with the most significant decline seen for lower-load modes. Reasons for poor combustion efficiency include positive valve overlap in the tested engine, as has been discussed in our earlier work [44], as well as cold areas of the combustion chamber as in the squish volume, as has been discussed in other dual-fuel engine studies [54,55]. Combustion efficiency declines were mitigated for the increased hydrogen mole fraction in the intake, as can be seen by comparing the bottom and top panels of Figure 5.…”
Section: Engine Efficiency and Combustion Performancementioning
confidence: 55%
See 1 more Smart Citation
“…Ammonia dual-fuel operation resulted in a sharp decrease in combustion efficiency for all modes, with the most significant decline seen for lower-load modes. Reasons for poor combustion efficiency include positive valve overlap in the tested engine, as has been discussed in our earlier work [44], as well as cold areas of the combustion chamber as in the squish volume, as has been discussed in other dual-fuel engine studies [54,55]. Combustion efficiency declines were mitigated for the increased hydrogen mole fraction in the intake, as can be seen by comparing the bottom and top panels of Figure 5.…”
Section: Engine Efficiency and Combustion Performancementioning
confidence: 55%
“…In that work, soot and NO x were both decreased to near-zero levels, at the expense of fuel consumption. In a later study, the same group [44] demonstrated both thermochemical recuperation and emissions reductions using ethanol steam reforming in a diesel-ethanol dual-fuel mode. For ammonia, Wang et al [13] explored the feasibility of an autothermal ammonia decomposition (ATD) system for diesel engines.…”
Section: Introductionmentioning
confidence: 95%
“…Dry reforming (with carbon dioxide) can provide the best recuperation, but it is vulnerable to rapid coking. Recently, Hwang et al [290] experimentally studied a "novel thermally incorporated steam reforming TCR reactor, which utilizes sensible and chemical energy in the exhaust to afford the required heat for hydrous ethanol steam reforming. Off-highway diesel engines were run at three different speeds and loads with diverging hydrous ethanol flow rates arriving fumigated energy fractions of up to 70%".…”
Section: Thermochemical Recuperationmentioning
confidence: 99%